Serbian Radicalism 1881–1903. Political Thought and Practice - Protić, Milan St. (Balcanica - Annual of the Institute for Balkan Studies, 2007)
Subject to transformation and change as any other political ideology, Serbian Radicalism nevertheless revolved round some more or less permanent concepts, the most important being constitutionalism, parliamentary democracy, civil liberties and local self-government. Yet another basic aspect of the Radical Party’s ideology, its national programme, may be seen as an external ingredient inasmuch as the national emancipation, liberation and unification of the Serbs were viewed as originating from internal freedom.It was only in the 1890s that their national programme became fully developed. Major features of the Party’s political practice, on the other hand,were flexibility, pragmatism and cohesion.